Advanced interoperable simulators for training in car terminals. (2015) - Nicoletti, Letizia; Chiurco, Alessandro; Spadafora, Francisco
The paper presents a simulation-based training framework for drivers and parkers in car terminals. Before going into the substance of the proposed training system an analysis of the current procedures used in car terminals as well as of the state of the art has validated the main idea the research work is underpinned by, confirming the potential benefits of modelling and simulation in such a dynamic and complex environment. The proposed solution, called CTSIM is made up of three interoperable simulators: an operator simulator, a ship simulator and a vehicle simulator. The vehicle simulator is able to simulate a medium car, a truck (tractor and trailer) and all the procedures performed by a driver in a car terminal while the operator simulator simulates all the movements and gestures of a parker with a high accuracy thanks to a technical solution which the Kinect, a tracking glove and a joystick are part of. The CTSIM simulators are integrated according to the paradigms of distributed and interoperable simulation so as to be able to share the same virtual environment while interacting each other.